Development of Mathematics Teaching Materials Based on Character Education in The New Normal Era - M Farid Nasrulloh; Eliza Verdianingsih; Indah Ismi Hayati (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this research is to design appropriate character education-based teaching materials to help students learn and train math skills. This research uses Research and Development method adapted in ADDIE model development. The subjects of this study were grade VIII of students at MTs Al-Ihsan Kalikejambon school year 2020/2021. The data collection techniques are interviews and questionnaires. Researchers designed a teaching material in the form of teaching materials based on character education. The results of this study showed that (1) Validation of character education-based teaching materials developed by expert assessments obtained a percentage of 80.4% with a fairly valid category. (2) The practicality of character education-based teaching materials by the assessment of math teachers obtains a percentage of 83.63% with a very practical category. (3) The response of students to teaching materials based on character education gets a percentage of 82.94% with a very practical category. Based on the results of the above study, the researchers concluded that character education-based teaching materials are declared valid and practical based on the assessment of experts and learners, so that character education-based teaching materials are eligible for use in mathematics learning.